Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1073/pnas.97.21.11575
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the human VPAC 2 receptor in the suprachiasmatic nucleus alters the circadian phenotype of mice

Abstract: The neuropeptides vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating polypeptide (PACAP) belong to a superfamily of structurally related peptide hormones that includes glucagon, glucagon-like peptides, secretin, and growth hormonereleasing hormone. Microinjection of VIP or PACAP into the rodent suprachiasmatic nucleus (SCN) phase shifts the circadian pacemaker and VIP antagonists, and antisense oligodeoxynucleotides have been shown to disrupt circadian function. VIP and PACAP have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 38 publications
(43 reference statements)
7
90
1
Order By: Relevance
“…It was proposed that these receptors in the cerebral cortex are involved in the regulation of energy metabolism. In the hypothalamus, VPAC 1 R is not expressed while VPAC 2 R is present at high levels in the suprachiasmatic nucleus and there was evidence suggesting the involvement of this receptor in regulating circadian rhythm (Piggins et al 1995, Shen et al 2000. In summary, our results are consistent with previous reports; the fVPAC 2 R homologue is widely distributed in both peripheral tissues and various regions of the brain.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It was proposed that these receptors in the cerebral cortex are involved in the regulation of energy metabolism. In the hypothalamus, VPAC 1 R is not expressed while VPAC 2 R is present at high levels in the suprachiasmatic nucleus and there was evidence suggesting the involvement of this receptor in regulating circadian rhythm (Piggins et al 1995, Shen et al 2000. In summary, our results are consistent with previous reports; the fVPAC 2 R homologue is widely distributed in both peripheral tissues and various regions of the brain.…”
Section: Discussionsupporting
confidence: 83%
“…VPAC 1 R is expressed almost exclusively in the cerebral cortex and hippocampus (Ishihara et al 1992) while VPAC 2 R has a wider distribution and is expressed in the olfactory bulb, hypothalamus, hippocampus, brainstem, pituitary and cerebellum (Lutz et al 1993, Usdin et al 1994, Sheward et al 1995. Interestingly, high levels of VPAC 2 R were detected in the suprachiasmatic nucleus and it is possible that this receptor is involved in the control of circadian rhythm (Piggins et al 1995, Shen et al 2000. Recently, a frog PACAP/VIP receptor (fPVR) (Alexandre et al 1999) which is structurally more related to the mammalian VPAC 1 Rs was isolated.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with control wild-types, these mutant mice show a shortened circadian period when maintained in constant dim red light and an increased rate of re-entrainment when the light-dark cycle is reset (Shen et al 2000). Moreover, Watanabe et al (2000) demonstrated that exogenous VIP reset the secretion of AVP from organotypic SCN cultures with a temporal pattern of sensitivity resembling that of a photic phase-response curve.…”
Section: Vip and Photic Entrainmentmentioning
confidence: 93%
“…Similar dim red light illumination is commonly used for monitoring locomotor activity in circadian studies (e.g. [4,5,7,[24][25][26]). We monitored locomotor activity and analysed circadian rhythms with the CLOCKLAB data acquisition and analysis system (Actimetrics Co., Wilmette, IL, USA).…”
Section: Methodsmentioning
confidence: 99%